2022
DOI: 10.3389/fendo.2022.880148
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Soluble TREM2 as a Potential Indicative Biomarker for Cognitive Impairment in Inadequately Controlled Type 2 Diabetes Without Obesity: The DOR-KyotoJ-1

Abstract: ObjectiveType 2 diabetes is a risk factor for dementia. We investigated whether serum levels of soluble triggering receptor expressed on myeloid cell 2 (sTREM2), a soluble form of the cell surface receptor TREM2, were predictive of cognitive impairment in type 2 diabetes without obesity.MethodsA total of 166 Japanese patients with type 2 diabetes without obesity were followed-up for 2 years. We measured clinical parameters, assessed cognitive function using the mini-mental state examination (MMSE), quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Diabetes deleteriously affects microglial function and results in cognitive impairment in both mouse models [ 11 , 42 , 43 ] and patients with T2DM [ 12 , 13 , 14 ]. Moreover, an HG environment elevated the intracellular ROS levels and triggered inflammatory responses in the microglia, which were implicated in several pathways including NF-κB signaling [ 17 , 18 ], p38 and SAPK/JNK MAPK pathways [ 19 ], and NLRP3 inflammasome activation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes deleteriously affects microglial function and results in cognitive impairment in both mouse models [ 11 , 42 , 43 ] and patients with T2DM [ 12 , 13 , 14 ]. Moreover, an HG environment elevated the intracellular ROS levels and triggered inflammatory responses in the microglia, which were implicated in several pathways including NF-κB signaling [ 17 , 18 ], p38 and SAPK/JNK MAPK pathways [ 19 ], and NLRP3 inflammasome activation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that GLP-1 receptor agonists have neuroprotective effects under diabetic conditions [ 10 , 11 ]. Diabetes-related microglial dysfunction is reportedly implicated in the cognitive impairment of patients with T2DM [ 12 , 13 , 14 ]. Although certain anti-diabetic medications, such as GLP-1 receptor agonists, may have beneficial effects on cognitive impairment, the therapeutic efficacy of these agents has not yet been established in humans [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings also revealed increased sTREM2 levels in the serum of long-COVID patients with cognitive impairment when compared to healthy controls ( Besteher et al, 2024 ), suggesting a corresponding shift in microglial reactivity in response to neuronal degeneration. In patients whose diabetes control deteriorated, those with higher baseline levels of sTREM2 experienced a more pronounced decline in Mini-Mental State Examination (MMSE) scores over a 2-year period, which suggests a potential link between higher sTREM2 levels and the acceleration of cognitive impairment under conditions of poor glycemic control ( Tanaka et al, 2022 ). This aligns with previous studies demonstrating an association between sTREM2 levels and neuronal injury markers in the early stages of AD.…”
Section: Strem2 Dynamics and Alzheimer’s Disease Progressionmentioning
confidence: 99%
“…In the general elderly Japanese population of the Hisayama study, higher levels of serum sTREM2 at baseline were found to be associated with an increased subsequent risk of both AD and VaD [20]. Furthermore, we recently demonstrated that higher levels of serum sTREM2 are cross-sectionally [21] and longitudinally [22] associated with an increased risk of diabetes-related cognitive impairment. In contrast, a recent longitudinal study of participants of the Dominantly Inherited Alzheimer Network (DIAN) found that higher CSF sTREM2 levels reduced the risk of AD pathologies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Second, not all cell types capable of releasing sTREM2 into the peripheral blood have been identified. Serum sTREM2 levels appear to reflect microglial activation [20] and it has been hypothesized that adipose tissue also produces sTREM2 [22]. The comprehensive identification of sTREM2-releasing cells and further cohort studies with larger sample sizes are needed to address these issues.…”
mentioning
confidence: 99%